Multicultural Education of Based Training at University of Muhammadiyah Malang - Khozin,; Akbar,; Sari, Eka Nur Maulida (International Journal of Psychosocial Rehabilitation, 2020)
– Multicultural education is an important aspect in facing the educational revolution 4.0. Education becomes a way to embed multicultural awareness to students by experiencing the multicultural process directly. The students are going to learn how to live and work together in a difference. This study aims to dig out how the implementation of multicultural education based on training at University of Muhammadiyah Malang. The subjects of this study were five Non-Muslim participants who had attended P2KK (Personality and Leadership Training Program) for a week. The instrument used was an intense interview and document review that were analyzed by using descriptive qualitative with a phenomenological approach. The results of this study indicates that Non-Muslim participants who joind the training were aware of their existence and ready to live and cooperate with other participants who had different belief or faith. In addition, they assumed that P2KK system is worthy for Non-Muslim participants without any discrimination.